Stability of local secondary structure determines selectivity of viral RNA chaperones - Bravo, Jack P K; Borodavka, Alexander; Barth, Anders; Calabrese, Antonio N; Mojzes, Peter; Cockburn, Joseph J B; Lamb, Don C; Tuma, Roman (Nucleic acids research, 2018)
To maintain genome integrity, segmented double-stranded RNA viruses of the Reoviridae family must accurately select and package a complete set of up to a dozen distinct genomic RNAs. It is thought that the high fidelity segmented genome assembly involves multiple sequence-specific RNA-RNA interactions between single-stranded RNA segment precursors. These are mediated by virus-encoded non-structural proteins with RNA chaperone-like activities, such as rotavirus (RV) NSP2 and avian reovirus σNS. Here, we compared the abilities of NSP2 and σNS to mediate sequence-specific interactions between RV genomic segment precursors. Despite their similar activities, NSP2 successfully promotes inter-segment association, while σNS fails to do so. To understand the mechanisms underlying such selectivity in promoting inter-molecular duplex formation, we compared RNA-binding and helix-unwinding activities of both proteins. We demonstrate that octameric NSP2 binds structured RNAs with high affinity, resulting in efficient intramolecular RNA helix disruption. Hexameric σNS oligomerizes into an octamer that binds two RNAs, yet it exhibits only limited RNA-unwinding activity compared to NSP2. Thus, the formation of intersegment RNA-RNA interactions is governed by both helix-unwinding capacity of the chaperones and stability of RNA structure. We propose that this protein-mediated RNA selection mechanism may underpin the high fidelity assembly of multi-segmented RNA genomes in Reoviridae.
Keywords: Base Sequence; Genome, Viral; Orthoreovirus, Avian; vazba proteinů; genom virový; proteiny vázající RNA; virové nestrukturální proteiny; RNA, Viral; Viral Nonstructural Proteins; Molecular Chaperones; Nucleic Acid Conformation; molekulární chaperony; ptačí orthoreovirus; konformace nukleové kyseliny; RNA virová; Models, Molecular; Protein Structure, Secondary; molekulární modely; sekvence nukleotidů; sekundární struktura proteinů; RNA-Binding Proteins; Protein Binding